Connecting medical records: an evaluation of benefits and challenges for primary care practices. Issue 2 (1st April 2017) - Compeau, Deborah R.; Terry, Amanda L.
Abstract : Background: Implementation of systems to support health information sharing has lagged other areas of healthcare IT, yet offers a strong possibility for benefit. Clinical acceptance is a key limiting factor in health IT adoption. Objectives: To assess the benefits and challenges experienced by clinicians using a custom-developed health information exchange system, and to show how perceptions of benefits and challenges influence perceptions of productivity and care-related outcomes. Methods: We used a mixed methods design with two phases. First, we conducted interviews with stakeholders who were familiar with the health information exchange system to inform the development of a measure of benefits and challenges of the use of this system. Second, using this measure, we conducted a survey of current and former users of the health information exchange system using a modified Dillman method. Data were analyzed using structural equation modelling, implemented in partial least squares. Results: 105 current and former users completed the survey. The results showed information quality, ease of completing tasks and clinical process improvement as key benefits that reduced workload and improved patient care. Challenges related to system reliability, quality of reports, and service quality increased workload and decreased impact on care, though the effect of the challenges was smaller than that of the benefits. Conclusion: Even very limited health information exchange capabilities can improve outcomes for primary care users. Improving perceptions of benefits may be even more important than removing challenges to use, though it is likely that a threshold of quality must be achieved for this to be true.